The Molecular Landscape and Biological Alterations Induced by PRAS40-Knockout in Head and Neck Squamous Cell Carcinoma - Chen, Gang; Li, Zhexuan; Chen, Changhan; Liu, Jiajia; Zhu, Weiming; She, Li; Huang, Huimei; Qin, Yuexiang; Liu, Guancheng; Wang, Juncheng; Liu, Yong; Huang, Donghai; et al. (Frontiers in Oncology, 2021)
PRAS40 (Prolin-rich Akt substrate of 40 kDa) is a critical protein that directly connects PI3K / Akt and mTORC1 pathway. It plays an indispensable role in the development of many diseases. However, the relationship of PRAS40 and head and neck squamous cell carcinoma (HNSCC) remains unclear. Here, our study indicated that high expression of PRAS40 mRNA is a favorable prognosis factor in HNSCC patients by analyzing 498 clinical and mRNA data. Moreover, we confirmed that CRISPR/Cas9 induced PRAS40-knockout would promote cell colony formation, migration, and invasion in several HNSCC cell lines. RNA-seq was employed to investigate the further possible mechanisms involving in the above regulations by PRAS40 in HNSCC cells. The molecular landscape contributed by 253 differential expressed mRNA after PRAS40-knockout were enriched in TGF-beta, PI3K-Akt, P53, mTOR, NF-kB signaling pathway. Partial molecular alternations within these pathways were validated by PCR or western blot. Besides, we found that high expression of PRAS40 in HNSC patients would present more CD8+ T and T follicular helper cells, but less Th17 cells than the patients with low expression of PRAS40. The altered molecular pathways and immune infiltrating cells might associate with the mechanism of PRAS40 being a suppressor in HNSCC cells, which would provide a potential prognosis predictor and therapeutic target in HNSCC patients.